Activation of dendritic cells by crosslinked collagen hydrogels (artificial corneas) varies with their composition. (18th July 2019) - Mölzer, Christine; Shankar, Sucharita P.; Griffith, May; Islam, Mirazul M.; Forrester, John V.; Kuffová, Lucia
Abstract: Activated T cells are known to promote fibrosis, a major complication limiting the range of polymeric hydrogels as artificial corneal implants. As T cells are activated by dendritic cells (DC), minimally activating hydrogels would be optimal. In this study, we evaluated the ability of a series of engineered (manufactured/fabricated) and natural collagen matrices to either activate DC or conversely induce DC apoptosis in vitro. Bone marrow DC were cultured on a series of singly and doubly crosslinked hydrogels (made from recombinant human collagen III [RHCIII] or collagen mimetic peptide [CMP]) or on natural collagen‐containing matrices, Matrigel TM and de‐cellularised mouse corneal stroma. DC surface expression of major histocompatibility complex Class II and CD86 as well as apoptosis markers were examined. Natural matrices induced low levels of DC activation and maintained a "tolerogenic" phenotype. The same applied to singly crosslinked CMP‐PEG gels. RHCIII gels singly crosslinked using either N ‐(3‐dimethylaminopropyl)‐ N ′‐ethylcarbodiimide with the coinitiator N ‐hydroxy succinimide (EDC‐NHS) or N ‐cyclohexyl‐ N ‐(2‐morpholinoethyl)carbodiimide metho‐ p ‐toulenesulfonate with NHS (CMC‐NHS) induced varying levels of DC activation. In contrast, however, RHCIII hydrogels incorporating an additional polymeric network of 2‐methacryloyloxyethyl phosphorylcholine did not activate DC but instead induced DC apoptosis, a phenomenon observed in natural matrices. This correlated with increased DC expression of leukocyte‐associated immunoglobulin‐like receptor‐1. Despite low immunogenic potential, viable tolerogenic DC migrated into and through both natural and manufactured RHCIII gels. These data show that the immunogenic potential of RHCIII gels varies with the nature and composition of the gel. Preclinical evaluation of hydrogel immunogenic/fibrogenic potential is recommended.